A nonfullerene acceptor incorporating a dithienopyran fused backbone for organic solar cells with efficiency over 14%. (September 2020) - Ke, Xin; Meng, Lingxian; Wan, Xiangjian; Cai, Yao; Gao, Huan-Huan; Yi, Yuan-Qiu-Qiang; Guo, Ziqi; Zhang, Hongtao; Li, Chenxi; Chen, Yongsheng
Abstract: An acceptor-donor-acceptor (A-D-A) type small molecule acceptor ITOT-4Cl incorporating a dithienopyran (DTP) fused backbone, has been designed and synthesized. With the strong electron-donating capability of the backbone D unit, ITOT-4Cl shows a narrow band gap of 1.28 eV, and has an efficient absorption in near-infrared region up to 968 nm. The photovoltaic devices based on PBDB-T:ITOT-4Cl give a power conversion efficiency (PCE) of 12.50%, with a high short circuit current density ( J sc ) of 22.89 mA cm −2 . With F–Br as the third component, the ternary organic solar cells device shows an enhanced PCE of 14.29% with an improved J sc of 24.40 mA cm −2, which is among the best results for oxygen heterocycle fused nonfullerene acceptor based devices. Graphical abstract: A small molecule acceptor ITOT-4Cl incorporating a dithienopyran fused backbone, has been designed and synthesized. ITOT-4Cl shows a narrow band gap of 1.28 eV owing to the strong electron donating capability of the fused backbone. The ternary OSCs exhibit a PCE of 14.29% with a high J sc of 24.40 mA cm −2, which is among the best results for oxygen heterocycle-fusion acceptors. Image 1 Highlights: A new acceptor ITOT-4Cl incorporating a dithienopyran fused backbone was reported. ITOT-4Cl shows a narrow band gap of 1.28 eV owing to the strong electron donating capability of backbone. The ternary OSCs exhibit a PCE of 14.29%, among the best results for oxygen heterocycle-fusion acceptors.